2016
DOI: 10.1364/oe.24.007133
|View full text |Cite
|
Sign up to set email alerts
|

SERS-active dielectric metamaterials based on periodic nanostructures

Abstract: New dielectric SERS metamaterial is investigated. The material consists of periodic dielectric bars deposited on the metal substrate. Computer simulations as well as real experiment reveal extraordinary optical reflectance in the proposed metamaterial due to the excitation of the multiple dielectric resonances. We demonstrate the enhancement of the Raman signal from the complex of 5,5'-dithio-bis-[2-nitrobenzoic acid] molecules and gold nanoparticle (DTNB-Au-NP), which is immobilized on the surface of the bars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Such pulsed electrical stimulation of AFM‐based fishing is possibly conditioned by a local increase of electric field gradient and induced magnetic field on HOPG in the vicinity of the mica surface. The effect of increasing electric field gradient can lead to possible excitations of plasmons in graphite, constituting the layers of highly conductive graphene flakes , and eddy currents can also be generated on the graphite surface . Besides, it should be noted that dielectric properties of the mica surface in the mica–graphite structure in their turn can influence the possibility of plasmon generation, and also change due to the changes in water structure on the surface of mica with immobilized probe molecules, as well as other electrokinetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Such pulsed electrical stimulation of AFM‐based fishing is possibly conditioned by a local increase of electric field gradient and induced magnetic field on HOPG in the vicinity of the mica surface. The effect of increasing electric field gradient can lead to possible excitations of plasmons in graphite, constituting the layers of highly conductive graphene flakes , and eddy currents can also be generated on the graphite surface . Besides, it should be noted that dielectric properties of the mica surface in the mica–graphite structure in their turn can influence the possibility of plasmon generation, and also change due to the changes in water structure on the surface of mica with immobilized probe molecules, as well as other electrokinetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of ultra-low proteins concentration in solution using novel physical effects like plasmonics, surface-enhanced Raman spectroscopy, and photonic waveguide-based sensors are promising techniques for novel medical diagnostics [1][2][3][4][5][6][7]. In particular, a low myoglobin concentration is a relevant marker of myocardial infarction in human blood plasma [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A strongly amplified electromagnetic field can be generated by disordered metal-dielectric composites in a broad spectral range [9]. Periodically ordered nanostructures enhance local EM field at selected frequencies [10,11,12,13,14,15,16,17,18,19,20,21,22,23]. Plasmon modes propagating in a chain of metallic nanoparticles, where the particle radius a is relatively equal to the distance δ between particles, are precisely investigated in [24].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al have showed an effective absorption of the EM field in periodic semiconductor metafilms for solar cells (see [72]). Some groups have demonstrated a strong electric field and SERS enhancement for periodic metafilms made of rectangular dielectric bars [12,16]. Sharp minima in the reflectance of the dielectric metasurface can be achieved in the microwave and optical domains.…”
Section: Introductionmentioning
confidence: 99%